Product-service system design for sustainability - Vezzoli, Carlo; Kohtala, Cindy; Srinivasan, Amrit; Diehl, J. C.; Fusakul, Sompit Moi; Xin, Liu (My University, 2017)
This book, based on a huge European and Asian research project, is a state-of-the-art examination of the theory and practice of system innovation through Product-Service System (PSS) design for sustainability from a trans-cultural viewpoint. PSS design incorporates innovative strategies that shift businesses away from simply designing and selling physical products to developing integrated systems of products and services that satisfy human needs. The book provides background, advice and tools for designers interested in sustainable PSSs and has a wealth of case studies for practitioners to digest.
Keywords: Collaborative services; Design thinking; Lca; Life cycle; Low income contexts; Product life cycle design; PSS; PSS design; Satisfaction unit; Sep; Siam cement group; Social innovation; Social innovation communities; Socio-ethical dimension; Stakeholder interactions; Sufficiency economy; Sustainable development; Sustainable PSS; System eco-efficiency; Waste pickers